2008
DOI: 10.1111/j.1745-6916.2008.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Enhancement: Food for Thought

Abstract: ABSTRACT-Self-enhancement denotes a class of psychological phenomena that involve taking a tendentiously positive view of oneself. We distinguish between four levels of self-enhancement-an observed effect, an ongoing process, a personality trait, and an underlying motiveand then use these distinctions to organize the wealth of relevant research. Furthermore, to render these distinctions intuitive, we draw an extended analogy between selfenhancement and the phenomenon of eating. Among the topics we address are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
485
2
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 673 publications
(527 citation statements)
references
References 199 publications
30
485
2
10
Order By: Relevance
“…In contrast, people who are low in intellectual humility have a lower tolerance for ambiguity (Leary et al, 2016), which may motivate them to avoid information that might raise questions about their existing viewpoints. Low intellectual humility is also associated with the tendency to be threatened by what one doesn't know (Krumrei-Mancuso & Rouse, 2016) and with the motive to defend one's ego in the face of ignorance, errors, disagreements, and other signs of one's intellectual shortcomings (Gregg, Sedikides, & Gebauer, 2011;Sedikides & Gregg, 2008). In contrast, people high in intellectual humility indicate that they enjoy finding out new information that differs from what they already think is true (Leary et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, people who are low in intellectual humility have a lower tolerance for ambiguity (Leary et al, 2016), which may motivate them to avoid information that might raise questions about their existing viewpoints. Low intellectual humility is also associated with the tendency to be threatened by what one doesn't know (Krumrei-Mancuso & Rouse, 2016) and with the motive to defend one's ego in the face of ignorance, errors, disagreements, and other signs of one's intellectual shortcomings (Gregg, Sedikides, & Gebauer, 2011;Sedikides & Gregg, 2008). In contrast, people high in intellectual humility indicate that they enjoy finding out new information that differs from what they already think is true (Leary et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…That work has shown that believing in oneself simply feels good (Marshall & Brown, 2008;Sedikides & Gregg, 2008). For example, self-confidence can improve self-esteem (Alicke, 1985), mental health (Taylor & Brown, 1988), and task motivation and persistence (Pajares, 1996).…”
Section: The Origins Of Overconfidencementioning
confidence: 99%
“…We are biased toward self-enhancement and justify our beliefs and actions-even altruistic action-in terms of self-interest, (Miller, 1999). Even beyond the "better-than-average" effect, our thinking is biased toward the self in comparison to others (Sedikides & Gregg, 2008). This is not mere egoism, for while we tend to think of ourselves as "better than average," we can also think of ourselves as below average in comparison to others (Kruger, 1999).…”
Section: §322 Accuracy and Accountabilitymentioning
confidence: 99%